Does gentle assisted pushing or giving birth in the upright position reduce the duration of the second stage of labour? A three-arm, open-label, randomised controlled trial in South Africa. Issue 3 (29th June 2018) - Hofmeyr, G Justus; Vogel, Joshua P; Singata, Mandisa; Habib, Ndema Abu; Landoulsi, Sihem; Gülmezoglu, A Metin
Abstract : Introduction: Gentle assisted pushing (GAP) is an innovative method of applying gentle, steady pressure to a woman's uterine fundus during second stage of labour. This randomised trial evaluated GAP in an upright position, compared with upright position alone or routine practice (recumbent posture). Methods: An open-label, hospital-based, randomised trial was conducted in Eastern Cape, South Africa. Randomisation occurred following at least 15 min in second stage of labour. Participants were randomly assigned (1:1:1) using computer-generated block randomisation of variable size using opaque, sealed, numbered envelopes. Primary analysis was intention to treat. Participants were healthy, nulliparous, consenting women with a singleton pregnancy in cephalic presentation where vaginal birth was anticipated. The primary outcome was mean time from randomisation to birth. Results: 1158 participants were randomly allocated to GAP (n=388), upright position (n=386) and routine practice (n=384), with no loss to follow-up. Baseline characteristics were largely similar. In the experimental arm, GAP was applied a median of two times (IQR 1.0–3.0). Women in upright position alone spent a median of 6 min (IQR 3.0–10.0) upright. Mean duration from randomisation to birth was not different across groups (mean (SD) duration: 24.1 (34.9) min in GAP group, 24.6 (30.5) min in upright group, 25.0 (39.3) min in routine practice group). There were no differences in secondary outcomes, except that at two sites maternal discomfort was greater for both GAP and upright position compared with routine practice; at the other sites there were no differences. Conclusion: No benefit was identified from GAP in the second stage; some women found the position uncomfortable. The use of fundal pressure should be limited to further research to determine techniques or settings in which it can safely assist vaginal birth. Women should be encouraged to assume the position they find most comfortable. Trial registration number: PACTR201502001034448.